INDONESIAN MUSLIMS IN THE PUBLIC SPHERE: A Review of Several Studies (JOURNAL OF INDONESIAN ISLAM, 2007)
Habermas’ idea of the public sphere as a space where members of society can develop discussions and debates on public issues has inspired some scholars to interpret the modern development of Muslim societies. The spread of communication technology that includes print and electronic media, has paved the way for the emergence of the public sphere in those societies. Several studies of Indonesian Islam by western scholars also pay attention to the public sphere. Having discussed those studies, this paper argues that, although Habermas’ very notion of the public sphere has been criticised and modified by the scholars, it can be used effectively and developed for further research on Indonesian Islam.